Analisis Hukum alih fungsi Tanah pertanian menjadi pembangunan Pemukiman dan Perumahan - Purba, Master Sahat; Idham, Idham (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
This research is a juridical analysis research on agricultural land that has changed functions for housing development by the local government. The transfer of agricultural land functions, especially in the district capital area, is in accordance with the regional spatial plan based on Regional Regulations. This is done for the smooth running of the government and to ensure the welfare of the people. The application of shifting the function of agricultural land for housing development is adjusted to the regional spatial plan. The policy taken regarding the transfer of agricultural land to non-agricultural functions of course still provides legal protection and pays attention to the rights of the community, especially people who work in the agricultural sector.